Aplikasi Pemesanan Ikan Di Tpi Palopo Berbasis Android - Nangke, Yasmi; Dani, Ahmad Ali Hakam; Suppa, Rinto (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The purpose of this research is to build an Android-based TPI Palopo Fish Ordering Application which is later expected to be able to assist and minimize the time used and facilitate the delivery of information. The type of research used is descriptive. The results of the study are in the form of an Android application consisting of several pages containing the order of TPI PALOPO fish, product information, product category information and product prices, all of which have been functionally tested using the black box testing method, and of course user friendly interface The software that supports this application uses the Windows 10 Android Studio operating system, XAMPP, Sublime Text, Photoshop CC 2015, Android emulator with UML as the system designer, which includes use case diagrams, activity diagrams, and sequence diagrams. The system development method applied is the waterfall, which is carried out step by step and must be passed sequentially. So that with this application that has been built, it is expected to improve the performance of an institution/agency/company, especially in TPI Palopo.